MBRS-49. USING SENSITIVE MAGNETIC RESONANCE IMAGING TECHNIQUES TO IMPROVE THE RISK STRATIFICATION OF PATIENTS WITH METASTATIC MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Mitoko, Christine; Linke, Franziska; Macarthur, Donald; Faas, Henryk; Coyle, Beth
Abstract: Medulloblastoma (MB) presents with metastasis in one-third of patients conferring a significantly poor prognosis. Unfortunately, current methods employed in risk stratification have limited sensitivity, with negative cerebrospinal fluid cytology and magnetic resonance imaging (MRI) in up to 50% of patients with histologically-proven metastases. Matrix metalloproteinases (MMPs) are enzymes secreted by tumour cells that can potentiate their dissemination. We hypothesised that the differential expression of MMP-2 and MMP-9, by a panel of sub-grouped MB cell lines, will correlate with their propensity to metastasise and that these differences are detectable using our synthesised 19 Fluorine-MMP-MRI biosensor. Gelatin zymography, western blotting, and qRT-PCR were performed to determine MMP-2 and -9 functional activity, as well as protein and gene expression levels in 7 sub-grouped medulloblastoma cell lines. The same samples were imaged using our 19 Fluorine-MMP-MRI biosensor. Our preliminary data shows that the expression of MMP-2 is upregulated in a recurrent group 4 MB cell line CHLA-01R MED compared to the matched isogenic primary CHLA-01 MED line at all levels. Additionally, an aggressive Group 3 cell line HD-MB03 repeatedly exhibited the highest levels of functionally active MMP-9 protein, and high MMP-2 gene expression at levels only comparable to the recurrent group 4 cell line. These findings suggest that MMP-2/-9 might be biomarkers for aggressive/metastatic MB. In order to achieve earlier, robust risk stratification of MB patients with disseminated disease, we aim to establish their potential as imaging biomarkers using our minimally-invasive, optimised 19 F-MMP-2/- 9 MRI biosensor. Thereby, facilitating the prompt provision of personalised adjuvant therapy.